Morphology Of A Sanguinicolid Blood Fluke, Sanguinicola Armata, In Grass Carp (Ctenopharyngodon Idella C. V.) Fingerlings And Its Prevalence - Ong, Bee Lee (1994)

(untitled)
Sanguinicola armata Plehn, 1905 is redescribed under light and Nomarski microscopy and SEM (Scanning Electron Microscopy). It is a lanceolate sanguinicolid with a single column of heavy lateral marginal spines; extensive vitellaria; long oesophagus and an X-shaped intestine with five-lobed caeca. There are 9-10 pairs of testes; median; post intestinal caeca and a single butterfly-shaped ovary. Male and female genital pores lie adjacent to each other, near to the posterior extremity. The uterus is short, post ovarian and contains only one egg.SEM study revealed minute, blunt spines at the posterior part of the proboscis and tiny posteriorly directed marginal spines at the posterior end which were not visible under the ordinary light and Nomarski microscopy. This had added extra taxonomical features to S. armata. Surface morphology of S. armata under SEM also showed many tegumental folds with ridges and crest, cilium-like structure and sensory papillae which may be related to their nutritional, sensory, excretory, secretory, osmoregulatory and immunological functions. Protrusion of the genital pores viewed under SEM helps to understand the fact that cross-fertilisation as being a rule in the trematodes' reproduction. The prevalence rate of infection of S. armata was found to be high (66.7%) in the locally produced grass carp (Ctenopharygodon idella) fingerlings in the farm under the present study. This was attributed to the abundance of aquatic snails which act as intermediate hosts of the fluke. However, the intensity of infection was low due to the host (immunological), environmental (stocking density and water chemistry) and parasite (reproductive biology) factors. Since the distribution of S. armata was highest (87.8%) in the bulbous arteriosus, it should be examined first for quick diagnosis of the fluke.